Para além do olhar : o ponto de vista no filme A mulher sem cabeça - Moreno, Vicente Nunes (2015)
This dissertation is aimed at mapping the debate around the point of view in cinema from a narratological genettian perspective, defining the agents responsible for the narrative, as well as its forms of subjective modulation - especially the triad focalization, ocularization and auricularization. The mapped concepts are then applied in the analysis of The Headless Woman (La Mujer Sin Cabeza, Lucrecia Martel, 2008), in an attempt to understand the narrative strategies employed in the film (mise en scène, mise en cadre, mise en chaîne) to reach an atypical subjective narration.